A microwave molten salt synthesis method of graphite phase carbon nitride / metal nitride composite catalytic material and its photocatalytic application

The graphite phase carbon nitride/metal nitride composite catalytic material was prepared by microwave molten salt synthesis method, which solved the problems of low electron conductivity and interface defects of graphite phase carbon nitride, and significantly improved the photocatalytic performance and CO2 reduction selectivity.

CN116422359BActive Publication Date: 2025-04-04UNIV OF SHANGHAI FOR SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310438203.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-23
Publication Date
2025-04-04
Estimated Expiration
2043-04-23

AI Technical Summary

Technical Problem

The efficiency of graphite phase carbon nitride in photocatalytic reactions is limited by its low electron conductivity, resulting in low separation and transfer efficiency of photogenerated carriers. The existing methods are prone to interfacial defects when increasing metal oxide loading, reducing photocatalytic performance.

Method used

The melted salt, graphite phase carbon nitride precursor and metal nitride precursor are mixed and microwave-heated to form graphite phase carbon nitride/metal nitride composite catalytic material. The melted salt promotes the crystallization of graphite phase carbon nitride and the dispersion of metal nitride through the melted salt, and improves electron conductivity and catalytic activity.

Benefits of technology

The electron conductivity and photocatalytic properties of graphite phase carbon nitride are improved, and the carrier separation and transfer efficiency in photocatalytic reactions are enhanced. Especially in CO2 photocatalytic reduction reactions, the selectivity and catalytic activity of reduction products are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116422359B_ABST
    Figure CN116422359B_ABST
Patent Text Reader

Abstract

The present invention relates to a microwave molten salt synthesis method of a graphite phase carbon nitride / metal nitride composite catalytic material and its photocatalytic application. The preparation method comprises: mixing a molten salt, a graphite phase carbon nitride precursor, and a metal nitride precursor, and performing a microwave molten salt synthesis reaction to obtain a composite catalytic material. Compared with the prior art, the present invention adopts a microwave molten salt synthesis method, which has the advantages of being simple, environmentally friendly, and efficient. At the same time, due to the use of a microwave heating method, rapid and uniform heating can be achieved, and the reaction temperature and reaction time can be controlled, thereby obtaining a graphite phase carbon nitride / metal nitride composite catalytic material with uniform particle size, high crystallinity, and many surface active sites. In the photocatalytic reaction, the catalytic material has good electronic conductivity, which is conducive to the generation, cross-interface transmission and separation of photogenerated carriers, and improves the kinetic characteristics of the catalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis and relates to a microwave molten salt synthesis method of a graphite phase carbon nitride / metal nitride composite catalytic material and a photocatalytic application thereof. Background Art

[0002] With the intensification of environmental problems and the growth of energy demand, photocatalytic technology has become a green energy conversion technology that has attracted much attention due to its high efficiency and environmental protection. In the CO2 reduction reaction, the performance of the photocatalyst has a crucial influence on the conversion rate and selectivity of CO2. Therefore, the search for efficient photocatalysts is one of the current research hotspots.

[0003] Graphitic carbon nitride (g-C3N4) is a material with good photocatalytic activity and chemical stability. Its band gap width is 2.7-2.8eV, and it can absorb light in the visible and ultraviolet regions. However, the efficiency of graphitic carbon nitride in photocatalytic reactions is limited by its low electronic conductivity, which restricts the separation and transfer of photogenerated carriers. Therefore, studying how to improve the electronic conductivity of graphitic carbon nitride and improve its photocatalytic performance has become a current research hotspot.

[0004] Currently, a common method is to load metal oxides on the surface of graphitic carbon nitride to enhance its electronic conductivity and photocatalytic activity. However, this method often leads to interface defects between metal oxides and graphitic carbon nitride, further reducing the photocatalytic performance.

[0005] Chinese patent CN105752953A discloses a method for preparing graphite phase carbon nitride, and the preparation process includes: using nitrogen-rich organic matter as raw material, using graphite or silicon carbide as microwave absorber, mixing nitrogen-rich organic matter and microwave absorber evenly, controlling the pressure to 5-35kPa, the power of microwave irradiation to 2-10kW, controlling the heating rate to 50-500℃ / min, and keeping the temperature at 450-700℃ for 5-30min to obtain graphite phase carbon nitride. This method is based on high-energy microwave irradiation treatment method, and can quickly and efficiently obtain graphite phase carbon nitride with a layered structure; and this method has the advantages of being simple and efficient, low cost, not using various expensive or environmentally harmful reagents such as catalysts, organic solvents, and protective gases, being environmentally friendly, and not requiring pretreatment of raw materials. It is a green preparation method that is conducive to large-scale commercial production. However, this method still has the problems of high preparation cost and poor photocatalytic performance. Summary of the invention

[0006] The purpose of the present invention is to provide a microwave molten salt synthesis method of a graphite phase carbon nitride / metal nitride composite catalytic material and its photocatalytic application.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A method for preparing a composite catalytic material, comprising:

[0009] The molten salt, the graphite phase carbon nitride precursor and the metal nitride precursor are mixed, and a microwave molten salt synthesis reaction is carried out to obtain a composite catalytic material.

[0010] Furthermore, the molten salt is one or more of KBr, NaBr, KCl or NaCl.

[0011] Furthermore, the graphite phase carbon nitride precursor is one or more of urea, thiourea, dicyandiamide or melamine.

[0012] Furthermore, the metal nitride precursor is a nitrate of one or more of Co, Ni, Mo, Fe, Cu, Cr, Zn, Ga, Mn or Ti.

[0013] Furthermore, in the microwave molten salt synthesis reaction, the microwave power is 50-2000W, the microwave frequency is 2-3GHz, and the reaction temperature is 300-800°C.

[0014] A composite catalytic material is prepared by the method as described above.

[0015] An application of a composite catalytic material comprises using the composite catalytic material to catalyze a CO2 photocatalytic reduction reaction.

[0016] Furthermore, in the CO2 photocatalytic reduction reaction, the reaction temperature is 20-80°C and the reaction time is 1-2h; the lighting conditions include: using a 200W xenon lamp to simulate sunlight, and by adding filters of different specifications, including AM1.5G, 420CUT and other filters, to achieve simulation of full spectrum, ultraviolet, visible light and near-infrared light sources.

[0017] An application of a composite catalytic material comprises using the composite catalytic material to catalyze the photocatalytic degradation reaction of organic matter.

[0018] Furthermore, in the photocatalytic degradation reaction, the reaction temperature is room temperature, and the lighting conditions include: using a xenon lamp as a light source.

[0019] The present invention promotes the crystallization of graphite phase carbon nitride by adding molten salt, and generates loaded metal nitride nanoparticles on its surface, thereby realizing efficient connection between graphite phase carbon nitride and metal nitride. Due to the addition of molten salt, the crystal structure of graphite phase carbon nitride is better maintained and stabilized, and metal nitride is also better dispersed and fixed, thereby generating higher catalytic activity in photocatalytic reaction. In addition, due to the K in molten salts such as KBr and KCl, K can be incorporated into graphite phase carbon nitride in the form of K ions during solid phase microwave heating, and the ability to provide electrons to graphite phase carbon nitride, more electrons participate in the photocatalytic reduction of CO2 reaction, so that the reduction product of CO2 is selectively CH4, and CH4 has a greater calorific value than CO, and has higher economic benefits.

[0020] In addition, the present invention also utilizes a microwave ion conductor heating mechanism, so that the molten salt can be heated more effectively, so that the reaction temperature can be quickly increased and uniformly heated, thereby facilitating the reaction. In addition, the present invention also preferably selects a graphite phase carbon nitride precursor and a metal nitride precursor to improve the photocatalytic performance of the prepared material.

[0021] In summary, the present invention proposes a method for preparing a novel graphite phase carbon nitride / metal nitride composite catalytic material, and utilizes its high reduction product selectivity, high carrier density, and effective carrier separation and transfer efficiency in the photocatalytic reduction of CO2 reaction, thereby solving the current problems of limited electron conductivity and catalytic activity in the photocatalytic reaction of graphite phase carbon nitride, and greatly improving the photocatalytic performance of graphite phase carbon nitride-based catalysts.

[0022] Compared with the prior art, the present invention has the following characteristics:

[0023] The present invention adopts a microwave molten salt synthesis method, which has the advantages of being simple, environmentally friendly, and highly efficient. At the same time, due to the use of a microwave heating method, rapid and uniform heating can be achieved, and the reaction temperature and reaction time can be controlled, thereby obtaining a graphite phase carbon nitride / metal nitride composite catalytic material with uniform particle size, high crystallinity, and multiple surface active sites. In the photocatalytic reaction, the catalytic material has good electronic conductivity, which is conducive to the generation, cross-interface transmission and separation of photogenerated carriers, and improves the kinetic characteristics of the catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TEM images (a)-(c) and selected area diffraction image (d) of the graphite phase carbon nitride / metal nitride (KPCN / CoN) composite catalytic material prepared in Example 7;

[0025] Figure 2The XRD spectrum of the graphite phase carbon nitride / metal nitride composite catalyst material prepared in Example 7;

[0026] Figure 3 These are the test results of the photocatalytic CO2 reduction performance of the graphite phase carbon nitride / metal nitride composite catalyst material prepared in Example 7. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] A method for preparing a composite catalytic material comprises the following steps:

[0029] S1: Grind the molten salt, graphite carbon nitride precursor, and metal nitride precursor thoroughly and evenly transfer them into a crucible (preferably a corundum crucible);

[0030] Wherein, the molten salt is one or more of KBr, NaBr, KCl or NaCl; the graphite phase carbon nitride precursor is one or more of urea, thiourea, dicyandiamide or melamine; the metal nitride precursor is one or more of nitrates of Co, Ni, Mo, Fe, Cu, Cr, Zn, Ga, Mn or Ti;

[0031] S2: using microwave ion conductor heating mechanism to heat and perform microwave molten salt synthesis reaction;

[0032] Among them, in the microwave molten salt synthesis reaction, the microwave power is 50-2000W, the microwave frequency is 2-3GHz, the reaction temperature is 300-800℃, and the reaction time is 30-60min;

[0033] S3: After cooling to room temperature, the powder product is washed with deionized water and anhydrous ethanol, centrifuged, and dried in a forced air drying oven at 60° C. for 12 hours to finally obtain a composite catalytic material.

[0034] When implementing the present invention, other additives such as surfactants, stabilizers, etc. may be added as needed to improve the performance and stability of the prepared graphite phase carbon nitride / metal nitride composite catalytic material.

[0035] The graphite phase carbon nitride / metal nitride composite catalytic material prepared by the present invention has good photocatalytic activity and stability, can be used in photocatalytic reactions, especially CO2 reduction reactions, and can improve the kinetic characteristics of catalytic reactions. The catalytic material has good electronic conductivity, is conducive to the generation, cross-interface transmission and separation of photogenerated carriers, and improves the kinetic characteristics of catalytic reactions.

[0036] In practical applications, the graphite phase carbon nitride / metal nitride composite catalytic material prepared by the present invention can be used to prepare new photocatalysts, photoelectrocatalysts, photocatalytic electrodes, etc., and can be used in the fields of photocatalytic degradation of organic pollutants, photocatalytic hydrogen production, photocatalytic reduction of CO2, etc.

[0037] The composite catalytic material prepared by the present invention has a higher CO2 adsorption capacity than single graphite phase carbon nitride or metal nitride material, so its catalytic activity in the photocatalytic CO2 reduction reaction is higher than single graphite phase carbon nitride or metal nitride material.

[0038] The CO2 photocatalytic reduction reaction includes reacting the composite catalytic material with CO2 under light conditions to reduce it to reduction products such as CO and CH4. The reaction conditions include: the reaction temperature is 20-60°C, and the reaction time is 1-2h; the light conditions include: the light conditions include AM1.5G light source, ultraviolet light source, visible light source and near-infrared light source; specifically, it includes: using a 200W xenon lamp to simulate sunlight, and by adding filters of different specifications, including AM1.5G, 420CUT and other filters, the simulation of full spectrum, ultraviolet, visible light and near-infrared light sources is achieved.

[0039] The photocatalytic degradation reaction includes reacting the composite catalytic material with other organic matter under light conditions to degrade them into harmless substances. The specific photocatalytic degradation reaction is: 20 mg of the catalyst is dispersed in 80 ml of RhB solution (30 mg / L) and stirred in the dark for 45 min to reach adsorption equilibrium. Under light conditions (200W xenon lamp), 2.5 ml of the suspension is taken and filtered every 5 min, and its absorbance is measured by a UV-visible spectrophotometer to determine the residual concentration of the pollutant. The KPCN / Mo2N synthesized in Example 3 shows a high degradation catalytic ability for RhB.

[0040] In some specific embodiments, the particle size of the composite catalytic material is between 1 and 100 nm, and the specific surface area is greater than 20 m 2 / g.

[0041] In some specific embodiments, the composite catalytic material can also be used in the fields of photocatalysis, photoelectrocatalysis, electrochemical catalysis, etc.; or in the fields of environmental protection, energy conversion, chemical synthesis, etc.; or can be used as the catalytic layer of devices such as dye-sensitized solar cells and photocatalytic water splitters.

[0042] The following embodiments are implemented based on the above technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0043] Embodiment 1:

[0044] Thiourea, Zn(NO3)2·6H2O, KBr, and KCl were weighed in a molar ratio of 25:1:1:1, mixed evenly, and placed in a microwave oven. At a microwave frequency of 2.45 GHz, a microwave power of 800 W, a microwave heating temperature of 550°C, and a reaction time of 60 min, a gray powder was obtained. The product was centrifuged, washed, and dried with deionized water and ethanol to obtain a KPCN / ZnN composite catalytic material.

[0045] Embodiment 2:

[0046] Weigh urea, Ni(NO3)2·6H2O, and KBr in a molar ratio of 25:1:2, mix them evenly, and put them into a microwave oven. At a microwave frequency of 2.45 GHz, a microwave power of 1000 W, a microwave heating temperature of 500°C, and react for 60 minutes to obtain a black powder. The product is centrifuged, washed, and dried with deionized water and ethanol to obtain a KPCN / Ni3N composite catalytic material.

[0047] Embodiment 3:

[0048] Weigh dicyandiamide, Mo(NO3)2·4H2O, KBr, and KCl in a molar ratio of 25:1:1:1, mix them evenly, and put them into a microwave oven. At a microwave frequency of 2.45 GHz, a microwave power of 1500 W, a microwave heating temperature of 600 ° C, and react for 30 minutes to obtain a black powder. The product was centrifuged, washed, and dried with deionized water and ethanol to obtain a KPCN / Mo2N composite catalytic material. A photocatalytic degradation experiment was carried out: 60 mg of the catalyst was dispersed in 150 ml of RhB solution (40 mg / L) and stirred in the dark for 45 minutes to reach adsorption equilibrium. Under illumination conditions (200 W xenon lamp), 3 ml of the suspension was taken and filtered every 5 minutes, and its absorbance was measured with a UV-visible spectrophotometer to determine the residual concentration of the pollutant. The KPCN / Mo2N synthesized in Example 3 showed high degradation catalytic ability for RhB.

[0049] Embodiment 4:

[0050] Melamine, Fe(NO3)3·9H2O, KBr, NaBr, KCl, and NaCl were weighed in a molar ratio of 25:1:1:1:1:1, mixed evenly, and put into a microwave oven. At a microwave frequency of 2.45 GHz, a microwave power of 2000 W, a microwave heating temperature of 500°C, and the reaction time was 60 min to obtain a black powder. The product was centrifuged, washed, and dried with deionized water and ethanol to obtain a KPCN / Fe3N composite catalytic material.

[0051] Embodiment 5:

[0052] Thiourea, Cu(NO3)2·3H2O, KBr, KCl, and NaCl were weighed in a molar ratio of 25:1:1:1:1, mixed evenly, and placed in a microwave oven. At a microwave frequency of 2.45 GHz, a microwave power of 800 W, and a microwave heating temperature of 500°C, the reaction was performed for 25 minutes to obtain a black powder. The product was centrifuged, washed, and dried with deionized water and ethanol to obtain a KPCN / Cu3N composite catalytic material.

[0053] Embodiment 6:

[0054] Thiourea, Cr(NO3)3·9H2O, KBr, NaBr, KCl, and NaCl were weighed in a molar ratio of 25:1:1:1:1:1, mixed evenly, and put into a microwave oven. At a microwave frequency of 2.45 GHz, a microwave power of 1000 W, a microwave heating temperature of 600°C, and a reaction time of 60 minutes, a black powder was obtained. The product was washed with ethanol, separated, and dried to obtain a KPCN / Cr2N composite catalytic material.

[0055] Embodiment 7:

[0056] Weigh 5g urea, 0.1g cobalt nitrate, and 0.2g KBr, mix them evenly, and put them into a solid-phase microwave heating furnace for microwave molten salt synthesis reaction. The microwave heating temperature is 550°C, the microwave power is 1200W, and the reaction time is 60min. After cooling to room temperature, take out the reaction product, wash it with deionized water and ethanol, separate it, and dry it to obtain a graphite phase carbon nitride / cobalt nitride composite catalytic material KPCN / CoN.

[0057] The obtained catalytic material KPCN / CoN was characterized, and the TEM image is as follows: Figure 1 (a)-(c) show cobalt-doped graphite-phase carbon nitride materials loaded with nano-scale cobalt nitride.

[0058] In addition, using the same method and process conditions, graphite phase carbon nitride (PCN) catalytic material was synthesized using only 5g urea as a precursor, KPCN catalytic material was synthesized using 5g urea and 0.2g KBr as precursors, and PCN / CoN composite catalytic material was synthesized using 5g urea and 0.1g Co(NO3)2 as precursors.

[0059] The obtained catalytic material was subjected to XRD analysis, and the XRD spectrum was as follows: Figure 2 As shown, a typical peak of graphite phase carbon nitride at 2θ=27.5° is displayed, and peaks of CoN at 2θ=36.2° and 42.1° are observed in the composite sample KPCN / CoN, proving that the prepared material is a KPCN / CoN composite material.

[0060] Application Example 1:

[0061] The photocatalytic CO2 reduction performance test was carried out on the catalytic material prepared in Example 7. The specific test process is as follows:

[0062] Take 20 mg of catalyst at the bottom of the reactor, add ethanol and disperse it evenly by ultrasonic, and dry it in a 60°C forced air drying oven to form a uniform catalyst film at the bottom of the reactor. Then place 84 mg of NaHCO3 in the groove on the side wall of the reactor and then exhaust the air in the reactor with N2. Continue to pass N2 for 15 minutes, then keep the reactor sealed, and use a syringe to inject 300 μL of 2M H2SO4 solution into the groove of the reactor to react with NaHCO3 to generate CO2 and H2O atmosphere, where the amount of CO2 and H2O is 1 mmol. Then irradiate with a 200W AM1.5G light source for 1 hour, and finally analyze the CO2 reduction product by gas chromatography. Its photocatalytic reduction performance of CO2 is as follows: Figure 3 As shown, PCN is pure graphite phase carbon nitride, KPCN is a catalyst material with only urea and KBr, KCl molten salts added, PCN / CoN is a catalyst material with only urea and Co(NO3)2 added, and KPCN / CoN is a catalyst material with urea, KBr, KCl molten salts and Co(NO3)2·6H2O added at the same time. Figure 3 It can be seen that KPCN changes the reduction selectivity of PCN to CH4. After CoN and KPCN are combined, the adsorption capacity of the composite catalytic material for CO2 is improved due to the addition of CoN with metal-like properties. The significant improvement in catalytic capacity is due to the fact that the loading of CoN provides more reaction sites. The catalytic performance of the catalytic material prepared by adding only Co(NO3)2·6H2O confirms that the change in selectivity is due to the introduction of K.

[0063] That is, the KPCN / CoN composite catalyst prepared by the present invention shows high selectivity in reducing CO2 to CH4 and excellent photocatalytic performance, indicating that the prepared graphite phase carbon nitride / cobalt nitride composite catalyst material has excellent catalytic activity.

[0064] Application Example 2:

[0065] 20 mg of KPCN / Mo2N synthesized in Example 3 was dispersed in 80 ml of RhB solution (40 mg / L) and stirred in the dark for 45 min to reach adsorption equilibrium. Under illumination (200 W xenon lamp), 3 ml of the suspension was taken and filtered every 5 min, and its absorbance was measured by UV-visible spectrophotometer to determine the residual concentration of the pollutant. KPCN / Mo2N synthesized in Example 3 showed high degradation catalytic ability for RhB.

[0066] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An application of a composite catalytic material, characterized in that: Composite catalytic materials are used to catalyze the photocatalytic reduction reaction of CO2; The preparation method of the composite catalytic material comprises: A molten salt, a graphite phase carbon nitride precursor, and a metal nitride precursor are mixed and subjected to a microwave molten salt synthesis reaction to obtain a composite catalytic material; the metal nitride precursor is cobalt nitrate, or a mixture of cobalt nitrate and one or both of nickel nitrate and zinc nitrate; The molten salt is one or a combination of KBr or KCl.

2. The use of a composite catalytic material according to claim 1, characterized in that: The molten salt also includes one or both of NaBr and NaCl.

3. The use of a composite catalytic material according to claim 1, characterized in that: The graphite phase carbon nitride precursor is one or more of urea, thiourea, dicyandiamide and melamine.

4. The use of a composite catalytic material according to claim 1, characterized in that: In the microwave molten salt synthesis reaction, the microwave power is 50-2000 W, the microwave frequency is 2-3 GHz, and the reaction temperature is 300-800°C.

5. The use of a composite catalytic material according to claim 1, characterized in that: In the CO2 photocatalytic reduction reaction, the reaction temperature is 20-80°C, the reaction time is 1-2h, and the lighting conditions include: using an AM1.5G light source.

Citation Information

Patent Citations

  • Preparation method of graphite phase carbonitride

    CN105752953A